The Ocean Economy in Mauritius : Making It Happen, Making It Last - Cervigni, Raffaello; Scandizzo, Pasquale Lucio (World Bank, Washington, DC, 2017)
The book aims at assessing the overall potential of the Ocean Economy (OE) to contribute to Mauritius' development, at identifying key sectoral and cross-cutting challenges to be overcome in order to seize that potential; and at evaluating ways to ensure the OE's longer-term sustainability, addressing in particular environmental and climate change concerns. While the book discusses specific projects in selected sectors, this is intended only to illustrate opportunities and challenges (including in terms of resource mobilization); an appraisal of the technicaland financial feasibility of individual projects would go beyond the scope of this work and would have to be conducted as part of separate follow-on activities. This book reflects data and information available as of March 31, 2017.